2019
DOI: 10.1002/tox.22722
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of pulmonary toxicity of benzalkonium chloride and triethylene glycol mixtures using in vitro and in vivo systems

Abstract: Benzalkonium chloride (BAC) is a widely used disinfectant/preservative, and respiratory exposure to this compound has been reported to be highly toxic. Spray‐form household products have been known to contain BAC together with triethylene glycol (TEG) in their solutions. The purpose of this study was to estimate the toxicity of BAC and TEG mixtures to pulmonary organs using in vitro and in vivo experiments. Human alveolar epithelial (A549) cells incubated with BAC (1‐10 μg/mL) for 24 hours showed significant c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 57 publications
0
17
0
2
Order By: Relevance
“…In addition, p53 arrests cell cycle via inducing p21 expression thereby allowing cells to recover, but, triggers apoptosis under the severe stress conditions [35,44]. It has been reported that BAC induces DNA damage and oxidative stress in human lung epithelial cells [14,16], suggesting that these cellular stress events promoted by BAC could be possible reasons for the increased expression of p53 ( Figure 3C). PARP catalyzes the transfer reaction of ADP-ribose for DNA repair, and this enzyme can be cleaved and inactivated by caspase-3 [45].…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…In addition, p53 arrests cell cycle via inducing p21 expression thereby allowing cells to recover, but, triggers apoptosis under the severe stress conditions [35,44]. It has been reported that BAC induces DNA damage and oxidative stress in human lung epithelial cells [14,16], suggesting that these cellular stress events promoted by BAC could be possible reasons for the increased expression of p53 ( Figure 3C). PARP catalyzes the transfer reaction of ADP-ribose for DNA repair, and this enzyme can be cleaved and inactivated by caspase-3 [45].…”
Section: Discussionmentioning
confidence: 92%
“…As a result, hydrophilic voids are created, phospholipids are solubilized, and finally the membrane structure is destroyed [2,4]. In alveolar and bronchial epithelial cells, BAC (1-100 μg/mL) treatment has been shown to induce acute cytotoxicity with cell membrane disruptions [14,16]. Inhalation of BAC damages airway epithelium resulting in the release of proteins and LDH to the bronchioalveolar spaces in rodents [11,12,15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, serious bronchoconstriction may be one of the major factors inducing death in mice immediately post-treatment. Although inflammatory response and oxidative stress were known to be induced by BAC [14,15], they were not associated with fatal outcomes. Effects of BAC on bronchoconstriction will be further investigated considering the possibility of neurotoxicity, which may interfere with respiration or cardiac function.…”
Section: Eahtmentioning
confidence: 93%